Exploring discrimination, social acceptance, and its impact on the psychological well-being of older men who have sex with men: A cross-sectional study - Alex Siu Wing Chan; Hok Bun Ku; Elsie Yan (BMC, 2024)
Abstract Background The exploration of discrimination, social acceptance, and their impact on the psychological well-being of older men who have sex with men (MSM) is a critical area of study within the broader field of LGBTQ+ research. This demographic, comprising individuals who identify as both male and homosexual and are aged in the older spectrum of the population, faces unique challenges that intersect age, sexual orientation, and societal attitudes. Objectives This study aimed to explore the relationship between social acceptance and isolation with discrimination and the impact on the psychological well-being of older MSM. Methods A cross-sectional survey was administered among older MSM residing in three distinct regions: the People's Republic of China (PRC), Hong Kong, and Taiwan, with a total sample size of N = 453 participants, evenly distributed with N = 151 individuals from each region. The survey included the General Health Questionnaire-12 (GHQ-12), the Discrimination and Self-Stigma Evaluation Scale (DSSES), and the Perceived Acceptance Scale (PAS) which measures the perceived social acceptance from friends, mother, father, and family. The data were analyzed using descriptive statistics, ANOVA, and regression analysis. Results The mean scores of the GHQ-12 indicated that the participants had a moderate level of psychological distress, with a mean score of 6.38 (SD = 2.55). The DSSES mean score was 27.78 (SD = 8.73), indicating that participants experienced discrimination in their everyday lives. The PAS mean score was 3.08 (SD = 0.48), indicating that participants had a moderate level of perceived social acceptance. These results suggest that discrimination and social acceptance differ among older MSM in different areas in PRC, Hong Kong, and Taiwan. Conclusions The study highlights the impact of discrimination and social acceptance on the psychological well-being of older MSM. The findings suggest that interventions aimed at reducing discrimination and promoting social acceptance may improve the psychological well-being of older MSM. These results have important implications for healthcare providers and policymakers in developing strategies to promote social acceptance and reduce discrimination towards older MSM.